Microscopic, serologic and molecular surveys on Dirofilaria immitis in stray dogs, Turkey - Simsek, Sami; Ozkanlar, Yunusemre; Balkaya, Ibrahim; Aktas, Mustafa Sinan (Elsevier Science Bv, 2011)
The prevalance of Dirofilaria immitis infection was evaluated in stray dogs of Erzurum, Turkey. A total of 123 whole-blood and 93 sera samples were collected from stray dogs older than 6 months were lived in animal shelter. The PCR and direct microscopic examinations were used for the detection of microfilaria and indirect-ELISA was performed for the detection of anti-D. immitis antibodies. The prevalence of D. immitis in the canine population was 8.1% by PCR, 2.1% by ELISA. In addition, microfilaria burdens of Dirofilaria sp. was 4.8% by direct blood smear examination. There was a statistical difference (P = 0.05) in the prevalence between males (10.5%) and females (2.3%) by direct blood smear examination. Similarly there was a statistical difference (P < 0.05) in the prevalence between males (15.8%) and females (4.7%) by PCR. Dogs belonging to the 0.5-1 years old group showed the highest prevalence than 2-4 ages group with three tests. Among the 93 samples screened by the ELISA, two samples were positive for the D. immitis antibodies. Both positive dogs with ELISA were females. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dirofilaria immitis; PCR; Microscopy; ELISA; Prevalance; Turkey